The profile of low back pain disability on laborers at Kendari Port Southeast Sulawesi - Marudin, Iriamana Liasyarah; HN, Rustam; Alifariki, La Ode; Kusnan, Adius (Universitas Aisyah Pringsewu, 2019)
Low back pain is unpleasant or painful condition that can lead to activity constraints. LBP is a major cause of disability in the world. Based on data from the Port Health Office in 2018, LBP is a condition that is often experienced by porters in Kendari’s Port. There are many factors that can affect lower back pain; such of the following is smoking. This study aims to determine the relationship between smoking degrees with disability of lower back pain. This research was an observational analytic study with a cross-sectional approach. 130 samples were obtained through total sampling. Data were analyzed using the Spearman correlation test (p less than 0.05). The Majority of respondents had mild smoking habits 70.8 percent and mild disabilities 42.3 percent. Based on statistical tests, a positive correlation between the degree of smoking and disability of lower back pain was obtained in porters in Kendari’s port with p value = 0,001 and a correlation coefficient = 0.524. There is a significant relationship between the smoking degrees and disability of low back pain in the porters of Kendari’s port.